BEBERAPA HASIL INOKULASI PADA CAKRAM DAUN KOPI DENGAN HEMILEIA VASTATRIX DI LABORATORIUM - Cipta Ginting , Abdul Gafur, dan Rusdi Evizal . (Universitas Lampung, 2002)
Some results of inoculations on coffee leaf disks with Hemileia vastatrix. Leaf rust caused by Hemileia vastatrix B. et Br. is the most important disease on coffee worldwide. The obligate nature of H. vastatrix limits research on the disease when inoculation or pathogen growth in laboratory is required. Inoculation on detached plant parts such as leaf disks may become an alternative to solve the problems. In this study, the procedure was tested using three coffee varieties (Kartika 1, USDA, and Robusta) as inoculum sources, leaves of different age, and different uredospore concentrations (4 x 103, 4 x 104, and 4 x 105 uredospores per ml suspension). The study was done in Laboratory of Plant Disease at University of Lampung from May to December 2001. Uredospores developed on leaves under field condition were used as inoculum. The uredospores were taken with sterilized scalpel and placed in sterilized distilled water. Before doing the experiments, the uredospores were measured using microscope equipped with a micrometer. The concentration of uredospore suspensions were prepared using hemacytometer. Leaf disks made with diameter of 2 cm were used in all inoculations. The results showed that the size of the uredospores varied greatly. The variation occurred not only among uredospores taken from different lesions or leaves but also among those taken from the same lesions. The size of almost all uredospores was the same as that reported in the literature. Uredospores taken from Kartika (but not from two other varieties) incited disease development and produced symptoms on leaf disks which were made from Kartika coffee. The age of leaves used to make leaf disks did not influence disease incidence. Uredospores concentration influenced (ï¡ = 0.05) disease incidence on leaf disks with higher concentration caused higher disease incidence .